The Effectiveness of Psychoeducation to Improve the Well-being of Parents Having Children with Autism During the Pandemic - Nurussakinah Daulay; Nefi Darmayanti (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study aimed to determine the role of group-based parenting support training with the psychoeducational method in improving the well-being of parents having children with autism spectrum disorders (ASD) during the pandemic. The participants were 10 parents divided into the psychoeducational group and 12 parents in the control group in one State Special School for Autism in Medan. The instrument used a scale based on seven aspects of subjective well-being, as expressed by White (2010). Furthermore, data analysis was carried out using an independent sample t-test. The results showed that there was no difference in the well-being score between the psychoeducational and control group (F (1,20) = 0.445, t = -0.446, p > 0.05). Meanwhile, the control group had higher well-being score in the post-test (n = 12, M = 103.17, SD = 16.596) than the psychoeducational group (n = 10, M = 100.20, SD = 14.148).